The modernity of others: Jewish anti-catholicism in Germany and France - Joskowicz, Ari (Stanford studies in Jewish history and culture, 2014)
Antisemitism, anti-Catholicism, and anticlericalism -- Jewish anticlericalism and the making of modern citizenship in the late Enlightenment -- Romanticism, Catholicism, and oppositional anticlericalism -- Reforming Judaism, defending the family : Jews in the Catholic-liberal conflicts at mid-century -- Jews in the transnational culture wars : secularism and anti-Papal rhetoric -- Representative secularism : Jewish members of parliament and religious debate -- Nationalism, antisemitism, and the decline of Jewish anti-Catholicism -- Conclusion : rethinking European secularism from a minority perspective